### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

f(t, x, y) → f(g(x, y), x, s(y))
g(s(x), 0) → t
g(s(x), s(y)) → g(x, y)

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
g(s(x), s(y)) →+ g(x, y)
gives rise to a decreasing loop by considering the right hand sides subterm at position [].
The pumping substitution is [x / s(x), y / s(y)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

f(t, x, y) → f(g(x, y), x, s(y))
g(s(x), 0') → t
g(s(x), s(y)) → g(x, y)

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
f(t, x, y) → f(g(x, y), x, s(y))
g(s(x), 0') → t
g(s(x), s(y)) → g(x, y)

Types:
f :: t → s:0' → s:0' → f
t :: t
g :: s:0' → s:0' → t
s :: s:0' → s:0'
0' :: s:0'
hole_f1_0 :: f
hole_t2_0 :: t
hole_s:0'3_0 :: s:0'
gen_s:0'4_0 :: Nat → s:0'

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
f, g

They will be analysed ascendingly in the following order:
g < f

### (8) Obligation:

TRS:
Rules:
f(t, x, y) → f(g(x, y), x, s(y))
g(s(x), 0') → t
g(s(x), s(y)) → g(x, y)

Types:
f :: t → s:0' → s:0' → f
t :: t
g :: s:0' → s:0' → t
s :: s:0' → s:0'
0' :: s:0'
hole_f1_0 :: f
hole_t2_0 :: t
hole_s:0'3_0 :: s:0'
gen_s:0'4_0 :: Nat → s:0'

Generator Equations:
gen_s:0'4_0(0) ⇔ 0'
gen_s:0'4_0(+(x, 1)) ⇔ s(gen_s:0'4_0(x))

The following defined symbols remain to be analysed:
g, f

They will be analysed ascendingly in the following order:
g < f

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
g(gen_s:0'4_0(+(1, n6_0)), gen_s:0'4_0(n6_0)) → t, rt ∈ Ω(1 + n60)

Induction Base:
g(gen_s:0'4_0(+(1, 0)), gen_s:0'4_0(0)) →RΩ(1)
t

Induction Step:
g(gen_s:0'4_0(+(1, +(n6_0, 1))), gen_s:0'4_0(+(n6_0, 1))) →RΩ(1)
g(gen_s:0'4_0(+(1, n6_0)), gen_s:0'4_0(n6_0)) →IH
t

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
f(t, x, y) → f(g(x, y), x, s(y))
g(s(x), 0') → t
g(s(x), s(y)) → g(x, y)

Types:
f :: t → s:0' → s:0' → f
t :: t
g :: s:0' → s:0' → t
s :: s:0' → s:0'
0' :: s:0'
hole_f1_0 :: f
hole_t2_0 :: t
hole_s:0'3_0 :: s:0'
gen_s:0'4_0 :: Nat → s:0'

Lemmas:
g(gen_s:0'4_0(+(1, n6_0)), gen_s:0'4_0(n6_0)) → t, rt ∈ Ω(1 + n60)

Generator Equations:
gen_s:0'4_0(0) ⇔ 0'
gen_s:0'4_0(+(x, 1)) ⇔ s(gen_s:0'4_0(x))

The following defined symbols remain to be analysed:
f

### (12) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol f.

### (13) Obligation:

TRS:
Rules:
f(t, x, y) → f(g(x, y), x, s(y))
g(s(x), 0') → t
g(s(x), s(y)) → g(x, y)

Types:
f :: t → s:0' → s:0' → f
t :: t
g :: s:0' → s:0' → t
s :: s:0' → s:0'
0' :: s:0'
hole_f1_0 :: f
hole_t2_0 :: t
hole_s:0'3_0 :: s:0'
gen_s:0'4_0 :: Nat → s:0'

Lemmas:
g(gen_s:0'4_0(+(1, n6_0)), gen_s:0'4_0(n6_0)) → t, rt ∈ Ω(1 + n60)

Generator Equations:
gen_s:0'4_0(0) ⇔ 0'
gen_s:0'4_0(+(x, 1)) ⇔ s(gen_s:0'4_0(x))

No more defined symbols left to analyse.

### (14) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
g(gen_s:0'4_0(+(1, n6_0)), gen_s:0'4_0(n6_0)) → t, rt ∈ Ω(1 + n60)

### (16) Obligation:

TRS:
Rules:
f(t, x, y) → f(g(x, y), x, s(y))
g(s(x), 0') → t
g(s(x), s(y)) → g(x, y)

Types:
f :: t → s:0' → s:0' → f
t :: t
g :: s:0' → s:0' → t
s :: s:0' → s:0'
0' :: s:0'
hole_f1_0 :: f
hole_t2_0 :: t
hole_s:0'3_0 :: s:0'
gen_s:0'4_0 :: Nat → s:0'

Lemmas:
g(gen_s:0'4_0(+(1, n6_0)), gen_s:0'4_0(n6_0)) → t, rt ∈ Ω(1 + n60)

Generator Equations:
gen_s:0'4_0(0) ⇔ 0'
gen_s:0'4_0(+(x, 1)) ⇔ s(gen_s:0'4_0(x))

No more defined symbols left to analyse.

### (17) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
g(gen_s:0'4_0(+(1, n6_0)), gen_s:0'4_0(n6_0)) → t, rt ∈ Ω(1 + n60)